Effect Analysis of Wearing an Lumbar Exoskeleton on Coordinated Activities of the Low Back Muscles Using sEMG Topographic Maps - Naifu Jiang; Dashuai Wang; Xinyu Ji; Lin Wang; Xinyu Wu; Guanglin Li (IEEE, 2024)
Lumbar exoskeleton has potential to assist in lumbar movements and thereby prevent impairment of back muscles. However, due to limitations of evaluation tools, the effect of lumbar exoskeletons on coordinated activities of back muscles is seldom investigated. This study used the surface electromyography (sEMG) topographic map based on multi-channel electrodes from low back muscles to analyze the effects. Thirteen subjects conducted two tasks, namely lifting and holding a 20kg-weight box. For each task, three different trials, not wearing exoskeleton (NoExo), wearing exoskeleton but power-off (OffExo), and wearing exoskeleton and power-on (OnExo), were randomly conducted. Root-mean-square (RMS) and median-frequency (MDF) topographic maps of the recorded sEMG were constructed. Three parameters, average pixel values, distribution of center of gravity (CoG), and entropy, were extracted from the maps to assess the muscle coordinated activities. In the lifting task, results showed the average pixel values of RMS maps for the NoExo trial were lower than those for the OffExo trial ( $\text{p} < 0.05$ ) but the same as those for the OnExo trial ( $\text{p}>$ 0.05). The distribution of CoG showed a significant difference between NoExo and OnExo trials ( $\text{p} < 0.05$ ). In the holding task, RMS and MDF maps’ average pixel values showed significant differences between NoExo and OnExo trials ( $\text{p} < 0.05$ ). These findings suggest that active lumbar exoskeletons can reduce the load on low back muscles in the static holding task rather than in the dynamic lifting task. This proves sEMG topographic maps offer a new way to evaluate such effects, thereby helping improve the design of lumbar exoskeleton systems.